CORRELATION BETWEEN PREGNANCY, POVERTY, AND COVID-19 DURING THE PANDEMIC IN INDONESIA - Irzameingindra Putri Radjamin; Raymond Lim; Puteri Riztin Perdanasari; Erisa Erisa; Olivia Margaretha Sugiarto; Natalisa Maragretha (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2022)
The COVID-19 pandemic has raised several social issues in every global sector. One of the social issues is the fluctuation of fertility rates that varies among developed and developing countries during the pandemic. This article examines the casual correlation between COVID-19, poverty, and pregnancy. This study seeks to understand whether there is either no correlation, one-way correlation, or two-way correlation between the variables by adopting the quantitative-descriptive method using a Pair-Wise Granger causality test. Even though COVID-19 raises concern for females to have a kid globally, Indonesia shows the opposite result that the pandemic affects pregnancy.